Chemical Composition and Evaluation of the Antimicrobial Activity of the Essential Oils from Fruits of Morinda lucida. Issue 4 (4th July 2018) - Prévost Kouamé, Bi Koffi François; Kablan, Landry; Djeda, Rodrigue; Toure, Daouda; Konan, Fernique; Tia, Vama Etienne; Moroh, Jean-Luc Aboya; Bedi, Gustave; Guessennd, Nathalie; Chalchat, Jean Claude; Tea, Illa; Robins, Richard; et al.
Abstract: The essential oils (EOs) obtained by hydro-distillation of fruits of Morinda lucida (Rubiaceae) growing in Côte d'Ivoire were investigated. The oil was analyzed and characterized by GC and GC-MS. Analyses of the EOs led to the identification and quantification of 45 constituents. Characterization of the EOs revealed the predominance of ( E )-phytol (14.80 %) and n -octanol (6.19 %) followed by β-caryophyllene (5.54 %) and 6, 10, 14-trimethyl pentandecan-2-one (5.48 %). The antibacterial activity of EOs from M. lucida was tested against three bacteria Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa using a disc-diffusion method and the minimal inhibitory concentration (MIC) values determined. The inhibition zones and MIC values were in the range of 11.6 to 24.3 mm and 32 to 256 μg/mL, respectively. The EOs showed good antibacterial activity against S. aureus and P. aeruginosa. The volatile oils extracted from M. lucida exhibited a higher activity than the antibiotics tested on P. aeruginosa .